(untitled) (Training and Practice : Journal of Educational Sciences, 2017)
The main conception of the Teachers’ Professional Career is the reflective teacher who is able to set goals as far as his/her professional development is concerned on the basis of his/her professional self-knowledge and reliable self-assessment. Reflection, Self-reflection and Self-assessment contribute to teachers’ adaptation, meeting challenges successfully along their professional career. Are Hungarian teachers aware of the idea of self-assessment? Do they ever assess themselves, if so, how does it contribute to their professional development? The empirical study to answer these questions makes us draw the conclusion, although self-assessment is a new pedagogical term for the Hungarian teachers, they guide their own professional development consciously by its extensive use.